Attitude towards of medical errors in Kazakhstan and in the world - Medet Toleubayev (National Scientific Medical Center, 2016)
Development of the issue of medical malpractice for professional offense acute medical and legal challenge facing modern healthcare. Question about this issue becomes relevant because of the need for social and legal protection of health workers and ensuring patients' rights. In the course of the historical development of the health systems of many developed foreign countries in connection with the improvement of the quality and complexity of the various medical procedures, our colleagues are always faced with the question of responsibility of doctors. First of all, it is connected with the development of insurance systems in health care. The development of industries such as legal services, democracy, transparency, empower patients and the transition to a partnership model of treatment has led to the emergence of various kinds of trials. In such processes, the doctor has always acted as a defendant. Increasing the number of such processes has prompted health organizations to study the problem of medical errors, which were aimed at preventing and reducing such processes.